HUBUNGAN KELOMPOK TEMAN SEBAYA, STRATEGI KOPING, DAN URUTAN KELAHIRAN DENGAN KECERDASAN SOSIAL PADA MAHASISWI TPB IPB - Farah, Amania; Krisnatuti, Diah; Herawati, Tin (Department of Family and Consumer Sciences, Faculty of Human Ecology, IPB University, 2013)
The research was to analyze the correlation of relationships of peer group, coping strategy, and birth order with social intelligence of undergraduate female student. This research involved 99 first grade undergraduate female students of Bogor Agricultural University that was choosed by cluster random sampling. Data was collected by self report and was analyzed by descriptive and inferensia statistics (one way ANOVA different test and Pearson correlation test). The results showed that undergraduate female student that was involved in this research had quality of relationship with peer group in adequate category, coping strategy in high category, and social intelligence in adequate category. Coping strategy of undergraduate female student differ significantly based on birth order. Birth order, peer group number (in class, dormitory, and other place), and quality of relationship with peer group correlated significantly with social intelligence.